2016
DOI: 10.1016/j.bjane.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of local anesthesia through lidocaine/ropivacaine on human melanoma cell lines

Abstract: LAs have cytotoxic activity on human melanoma cell lines in a time-, concentration- and agent-dependant manner. Apoptosis in the cell lines was mediated through activity of caspases-3 and caspases-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…In this present study, we found that ropivacaine and lidocaine but not bupivacaine resulted in significant inhibitions of cell migration and growth, and induction of cell apoptosis in melanoma. This is consistent with the previous study showing the cytotoxic effects of local anesthesia through lidocaine and ropivacaine on a human melanoma cell line [25]. Our study further extends the previous study by showing that 1) bupivacaine is not toxic to melanoma cells; 2) local anesthetics have differential effects on the varying biological activities of melanoma cells; and 3) the molecular mechanisms are via targeting small GTPases.…”
Section: Discussionsupporting
confidence: 92%
“…In this present study, we found that ropivacaine and lidocaine but not bupivacaine resulted in significant inhibitions of cell migration and growth, and induction of cell apoptosis in melanoma. This is consistent with the previous study showing the cytotoxic effects of local anesthesia through lidocaine and ropivacaine on a human melanoma cell line [25]. Our study further extends the previous study by showing that 1) bupivacaine is not toxic to melanoma cells; 2) local anesthetics have differential effects on the varying biological activities of melanoma cells; and 3) the molecular mechanisms are via targeting small GTPases.…”
Section: Discussionsupporting
confidence: 92%
“…However, these concentrations are not representative of the steadystate concentrations in vivo and Hirata et al 19 reported suppression of human corneal epithelial cells by treatment with lidocaine at concentrations as low as 400 µM. 17 We then investigated the effects of lidocaine on melanoma cell signaling pathways to provide a greater understanding of the antiproliferative mechanism. Flow cytometric cell cycle analysis revealed that lidocaine caused cell-cycle arrest in the G1 phase, although this effect did not appear to be concentration-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…9,19,21 Moreover, amino amide local anesthetics have recently been shown to induce apoptosis in human melanoma cell lines. 17 We then investigated the effects of lidocaine on melanoma cell signaling pathways to provide a greater understanding of the antiproliferative mechanism. Chang et al 20 demonstrated modulation of the mitogen-activated protein kinase/ERK signaling by lidocaine in thyroid cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“… Kang et al (2016) found that lidocaine (2%), ropivacaine (0.75%), and their combination exhibited cytotoxic effects to melanoma cell lines A375 and Hs294T cells via the induction of apoptosis, and this effect was mediated through the activation of caspase-3 and caspase-8.…”
Section: Lidocaine In Cancer Treatmentmentioning
confidence: 99%